Analisis Penggunaan Media Kata Bergambar Dalam Meningkatkan Keterampilan Membaca Siswa kelas 6 Melalui Model Pembelajaran Kooperatif Integrated Reading And Composition Circ Di SDN 130/ll Pasir putih - Sela (JRPD (Jurnal Riset Pendidikan Dasar), 2026)
The purpose of this study is to describe the improvement of the beginning reading ability of grade 2 students of SDN 130/ll Pasir Putih. The type of research used in this study is This study uses classroom action research (CAR). The place and time of this study were at SDN 130/ll Pasir Putih on May 22, 2023. The research subjects used in this study were 27 grade 2 students. Data collection techniques used in this study were observation, tests and documentation. The results of the study indicate that in improving reading ability through picture card media in grade II students of SDN 130/ll Pasir Putih can be applied. This can be seen from the average value of learning outcomes in cycle I, there were 17 students (62%) who completed the beginning reading using picture card media in grade II of SDN 130/ll Pasir Putih and cycle II became 23 students (85%) who completed understanding the beginning reading ability with the application of picture card media in grade II students of SDN 130/ll Pasir Putih.